Understanding qualitative research and ethnomethodology - Have, Paul ten, 1937- (Online access: SAGE SAGE Research Methods Core., 2004)
A supplementary textbook for advanced courses in both ethnomethodology and qualitative research methods in sociology, anthropology, communications, and professional education. It assumes a basic familiarity with qualitative research methods and hopefully with ethnomethodology.